An evaluation on the impact of internal marketing strategies on organizational performance - Misheck, Leonard (Midlands State University, 2017)
This study sought to analyze the impacts of internal marketing on organizational performance a case of SAZ for the period of 2013 to 2015. The researcher assumes that the chosen branch used for the study fairly represented all SAZ branches around Zimbabwe. The research sets to determine the contribution of employee training on service delivery, to explore the effectiveness of internal communication on employee performance and to ascertain the effect of job enrichment on employee performance. Descriptive research design was used for the study. The researcher assumes that internal marketing will improve company performance and the company is committed to continuously motivate its employees. In carrying out the research, descriptive research design was used. The population under the study was 50employees.The researcher used a sample size of 33 respondents and the sample size was determined using the de Vaas formula. Probability and non-probability sampling methods were used in carrying out the research. In data collection, the researcher used a primary data source that is questionnaires to gather the much needed information from the field. Secondary data sources were also used in carrying out the research. In analyzing the data, the researcher used Microsoft excel. Qualitative techniques were used for presenting the data gathered. To come out with clearly presented data, the researcher used pie charts and graphs to present the data. From the research, it was noted that internal marketing has a positive inverse relationship with organizational performance. It was noted that SAZ as an organization, thrives to keep its employees updated about market changes through offering various training courses to the employees. The research reviewed that there is strong internal communication networks within the organization. In addition some employees indicated that job enrichment is import for them to be satisfied with their work. The researcher used training, internal communication and job enrichment as the variables of internal marketing. In carrying out the research, the researcher came across various constraints such as limited funds and limited time among others. However besides these limitations, a summary, conclusions and recommendations were drawn from the research.